Politics, economy, and society writings and lectures, volume 4 - Ricœur, Paul; Monteil, Pierre-Olivier 1959-; Blamey, Kathleen (Cambridge, [England] Polity Press, 2021)
"The key political writings of one of the leading philosophers of the 20th century"--Provided by publisher.
Includes bibliographical references and index.
"Originally published in French as politique, économie et société. Ecrits et conferences, 4, ©Editions du Seuil, 2019."
Keywords: Political science -- Philosophy; Political ethics